Ranking banks using K-Means and Grey relational method - Seyed Abdoreza Tahami Pour Zarandi; Vahid Shahabi; Mohammad Emami; Atefeh Rezaee; Mehdi Hassanloo (Management Science Letters)
Research has been done on evaluating the performance more emphasis either on the technical aspects of the performance evaluation or considers only one aspect of banks such as sales, revenue, etc. This paper presents an empirical investigation to measure the relative efficiency of different banks using a hybrid of K-means and Grey relational analysis. The study uses eight criteria such as resources, customer satisfaction, etc. for clustering different banks and using Grey relational analysis provides ranking of different branches of a bank named Bank Qarzol Hasane Resalat located in city of Tehran, Iran. The preliminary study has indicated that the proposed model of this paper may capable of providing some promising results.